Forced Orthodontic Eruption of Impacted Maxillary Canine: A Case Report (Nepal Journal of Health Sciences, 2022)
Maxillary canines affect the smile and facial esthetics providing upper lip and alar base support. This article presents the case report of skeletal class I malocclusion with Angle’s class III (Right) subdivision and impacted left maxillary canine of poor prognosis for traction which was managed successfully with a combined surgical and orthodontic approach. The diagnosis of the impaction was done through the Orthopantogram, intra-oral periapical, and occlusal radiographs and was localized buccally through clinical examination and Clark’s technique. The impacted canine was brought into the arch which improved the smile and self-esteem of the patient.